Antecedents and outcomes of team processes. - Kuan, Tjian Titus. (2008)
This project explores the antecendents and outcomes of team processes. This study sought to investigate the effects of the four dimensions of justice antecedents on the team processes of team commitment, collective esteem, instrumentality and helping behavior. This would be followed by how such processes impact team outcomes, which is measured by team effectiveness and group solidarity.